The varieties of Confucian experience: documenting a grassroots revival of tradition - Billioud, Sébastien (Religion in Chinese societies, 2018)
Although the development of a "popular" brand of Confucianism in China is today a massive phenomenon, research on the topic remains scarce. Based on fieldwork carried out by a team of scholars in different parts of the country, the ambition of The Varieties of Confucian Experience is to contribute to the limited body of ethnographic accounts that aim to document and understand the diversity of phenomena encapsulated under the label "Confucian revival" in the first two decades of the 21st century.